Inconstitucionalidades de la Ley Orgánica de Garantías Jurisdiccionales y Control Constitucional y otras falacias jurídicas - Ernesto López Freire (Universidad Hemisferios, 2010)
This paper demonstrates the various unconstitutional and fallacies of the Organic Law of Judicial guarantees and Constitutional Control. For that, there will be a comprehensive collation between the mentioned law and the Constitution of the Republic of Ecuador and force. Through this analysis shows a lack of knowledge of Ecuadorian law or legal science by their authors. This study elucidated, inter alia, the inconsistencies in matters relating to the interpretation of constitutional provisions, full compensation, material and integral; challenge administrative acts, judicial unit.